ESTIMATION OF PROFITABILITY FACTORS OF MILL COMPANIES IN VOJVODINA - Tekić, Dragana (Journal on Processing and Energy in Agriculture, 2022)
The subject of this research are mill companies that operated on the territory of Vojvodina in 2019. The aim of the research is to assess the profitability of the observed companies, as well as financial indicators that affect profitability. A sample of 23 small and medium-sized mills was taken and profitability indicators were calculated: return on assets and return on capital, as well as financial indicators: liquidity, indebtedness, solvency and productivity. Based on the calculated indicators of descriptive statistics, it was determined that the median value of the return on assets was 2.58%, and the median value of the return on capital was 5.56%. The influence of factors on profitability was analyzed by applying regression analysis, and the return on assets and return on capital appeared as dependent variables in the models. The significance of the formed regression models was tested by applying regression variance analysis and it was determined that the model containing the return on assets as a dependet variable is statistically significant, while the model containing the return on capital as a dependent variable is not statistically significant. Of the observed profitability factors, only the indebtedness indicator stood out as significant.
Keywords: profitability, mill companies, food industry, regression analysis, Vojvodina